2010
DOI: 10.1177/0363546509352460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Functional and Structural Outcome after Rotator Cuff Repair

Abstract: On univariate analysis, older age was related with poor postoperative integrity and better functional improvement in Constant score. Multivariate regression revealed that age was not an independent determinant for anatomical or functional outcome whereas the tear retraction and fatty degeneration of the infraspinatus were independent factors for the integrity of repair and the presence of the paradoxical abduction and abduction torque of the unaffected shoulder for the Constant score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(57 citation statements)
references
References 46 publications
(77 reference statements)
3
51
3
Order By: Relevance
“…Chung et al [15] , in another study of 108 patients who underwent arthroscopic repair of massive rotator cuff tears, found that while several factors were associated with failure of cuff healing in the univariate analysis including age, only fatty infiltration was significantly related to healing failure in the multivariate analysis. Similarly, Oh et al [13] noted that age was not an independent predictor of tendon healing or functional outcome. Tear retraction and fatty atrophy were found to be the only independent predictors of tendon healing in their study [13] .…”
Section: Agementioning
confidence: 96%
See 4 more Smart Citations
“…Chung et al [15] , in another study of 108 patients who underwent arthroscopic repair of massive rotator cuff tears, found that while several factors were associated with failure of cuff healing in the univariate analysis including age, only fatty infiltration was significantly related to healing failure in the multivariate analysis. Similarly, Oh et al [13] noted that age was not an independent predictor of tendon healing or functional outcome. Tear retraction and fatty atrophy were found to be the only independent predictors of tendon healing in their study [13] .…”
Section: Agementioning
confidence: 96%
“…Similarly, Oh et al [13] noted that age was not an independent predictor of tendon healing or functional outcome. Tear retraction and fatty atrophy were found to be the only independent predictors of tendon healing in their study [13] . Therefore, age may be a surrogate for other anatomical factors correlated with impaired healing after rotator cuff repair.…”
Section: Agementioning
confidence: 96%
See 3 more Smart Citations